FIQIH PERUBAHAN UNTUK PEREMPUAN (Upaya Menjawab Keusangan dan Kekosongan Hukum bagi Perempuan) - Zulfatun Ni'mah (UIN K.H. Abdurrahman Wahid Pekalongan, 2009)
The change is an absolute process in all aspects of life. Human as actor of this life witnesses this process, much more women. Because of being made in ancient time, law oftern come late other contemporary events. Law on women are lagged, behind unable to keep abreast with wheels of changes. Hence it seems absolute and void which leads to obtaining laws legimitation over their choosen deeds as a result of the changes, event if they prompt to utilize the old law, they are threaten with sins, prohibition and hell. A new law formulation that accomadating to women’s need is unavoidable. Much less their voices, thoughts, feelings, and experiences should be a sourced of deliberation in regulating new Islamic law (fiqih) so as to bring no fault any longer as it was being formatted which mens dominanace